Spatial variation of surface water quality of Bera lake system using water quality index (WQI) & national water quality standard (NWQS) Malaysia - Nur Musfirah, Muhamad Din (2018)
A study on the spatial variation of surface water quality of the Bera Lake system was conducted at three sampling stations which were at agriculture area, resort area and jetty area. A total of eighteen water quality parameters were analyzed including in-situ test and laboratory test. All the parameters were analyzed and measured according to standard method. Water quality parameters were classified based on Department of Environment Water Quality Index and National Water Quality Standard (NWQS) for Malaysia. The physical, chemical and biological variables were temperature, turbidity, total suspended solid (TSS), dissolved oxygen (DO), pH, biological oxygen demand (BOD), chemical oxygen demand (COD), electrical conductivity (EC), ammoniacal nitrogen, nitrate, phosphate, total coliform, and Escherichia coli (E.Coli). The results show that water quality at Bera Lake was under Class II based on WQI, which means, Bera Lake is suitable for recreational activity and body contact is allowed, however basic treatment required for water supply. Based on NWQS, electrical conductivity (EC), total suspended solid (TSS), ammoniacal nitrogen are under class I and nitrate were Class II. Parameter for turbidity, phosphate, biochemical oxygen demand (BOD) were under class (III) and chemical oxygen demand (COD) was under Class II. pH and dissolved Oxygen were under Class III. BOD was higher at agriculture area (7.45mg/L) and low at resort area (1.15 mg/L), so BOD was under class III. While, for COD the higher value was at resort area (14.5 mg/L) and lower at agriculture area (10.25mg/L), so COD was under class II. For total suspended solid (TSS), higher value was at agriculture area (23.00 mg/L) and lower at jetty area (4.00 mg/L), so TSS was under class I. Human activities at surrounding area near Bera Lake affected water quality there. Agricultural activity, such as palm oil plantation, indeed affects water quality in Bera Lake and if these situation continued, may have caused environmental degradation at Bera Lake hence may lead algal bloom in lakes.